Analysis of Two-stage Quantizer with Embedded G. 711 Quantizer and Segmental Uniform Quantizer - Perić, Z.; Nikolić, J.; Lukić, J.; Denić, D. (Elektronika ir Elektrotechnika, 2013)
In this paper a novel two-stage quantizer with the embedded G.711 quantizer is proposed for speech signal processing. The first processing stage, where the input signal is quantized with the G.711 quantizer, is followed by the second stage where the segmental uniform quantizer performs the reduction of the quantization error introduced in the first stage. In this way higher signal quality, measured by signal to quantization noise ratio, is achieved in comparison with the G.711 quantizer while no bit rate reduction is performed. Particularly, in the second stage two additional bits are introduced. Although the expected quality gain, as a result of increasing the overall bit rate for 2 bit/sample, is around 12 dB, the gain achieved with the proposed quantizer is 14 dB. This additional quality gain of 2 dB proves the advantage of the proposed two-stage quantizer. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.1107